“A gente não está preparado para ser professor”: efeitos discursivos da disciplina de libras nas licenciaturas da UFSM - Elsner, Raisa de Matos (2020)
This dissertation was developed alongside the Graduate Program in Education of the Federal University of Santa Maria (UFSM), within the research field of Special Education, Inclusion and Difference and had as its main goal to understand the discursive effects produced in the discipline of Libras taught in licentiate degree courses from UFSM. From a post-structuralist perspective of Education, the research aimed at having a postmodern ethnographic approach for the production and analysis of materialities, and from them, the following conceptual tools were listed: discourse (Michel Foucault); experience and craftsmanship (Jorge Larrosa). The materiality produced consisted of, among other crossings inherent to an ethnographic research, the narratives of undergraduate students, recorded in a field journal. During the research, it was noticed that, in addition to teaching a language, mandatory in teacher formation courses since the Decree no. 5.626 of 2005, the discipline of Libras in Licentiate Degree Courses can be a place for other crossings, namely: the relationship with Difference, the process of becoming a teacher and the power of the school. Based on the conceptual tools listed, it was possible to visualize the discursive formation which involves the teachers’ formation process in different bodies of knowledge, as well as thinking about teaching teachers from what Larrosa (2018) understands as a teacher’s profession. Aligned with this, the power of the school as a meeting and experience place is highlighted, as well as the importance of the teacher's role in their capacity to produce listening.